Epithelial Cell Damage Activates Bactericidal/Permeability Increasing-Protein (BPI) Expression in Intestinal Epithelium - Balakrishnan, Arjun; Chakravortty, Dipshikha (Frontiers in Microbiology, 2017)
As the first line of defense against invading pathogen, intestinal epithelium produces various antimicrobial proteins (AMP) that help in clearance of pathogen. Bactericidal/permeability-increasing protein (BPI) is a 55kDa AMP that is expressed in intestinal epithelium. Dysregulation of BPI in intestinal epithelium is associated with various inflammatory diseases like Crohn’s Disease (CD), Ulcerative colitis (UC) and Infectious enteritis’s. In this paper, we report a direct correlation between intestinal damage and BPI expression. In Caco-2 cells, we see a significant increase in BPI levels upon membrane damage mediated by S.aureus infection and pore-forming toxins (Streptolysin and Listeriolysin).Cells detect changes in potassium levels as a Danger-associated molecular pattern (DAMP) associated with cell damage and induce BPI expression in a p38 dependent manner. These results are further supported by in vivo findings that BPI expression in the murine intestinal epithelium is induced upon infection with bacteria which cause intestinal damage (Salmonella Typhimurium and Shigella flexneri) whereas mutants that didnot cause intestinal damage (STM ΔfliC and STM ΔinvC) didnot induce BPI expression. Our results suggest that epithelial damage associated with infection act as a signal to induce BPI expression.